The Influence Of Fundamental And Macroeconomic Factors On Stock Prices In The JII (Jakarta Islamic Index) - Syafrina Yuni Lubis; Nurbaiti Nurbaiti; Rahmi Syahreza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to analyze the influence of fundamental and macroeconomic factors on stock prices in companies listed on the JII (Jakarta Islamic Index). This study uses a quantitative approach and secondary data obtained from the official JII (Jakarta Islamic Index) website. Data was processed using the Eviews_8 for Windows program with the technique of multiple linear regression analysis. The results of this study indicate that BVS (Book Value Per Share), DER (Debt Equity Ratio), EPS (Earnings Per Share), inflation, and interest rates partially influence stock prices. Furthermore, BVS, EPS, DER, inflation, and interest rates simultaneously affect stock prices. The coefficient of determination (R²) is 0.781413. This result shows that BVS, EPS, DER, inflation, and interest rates together have a proportionate influence on stock prices of 78.14%, while the remaining portion is influenced by other variables not included in this linear regression model.